Segregating patterns of copy number variations in extended autism spectrum disorder (ASD) pedigrees. Issue 5 (6th May 2020) - Woodbury‐Smith, Marc; Zarrei, Mehdi; Wei, John; Thiruvahindrapuram, Bhooma; O'Connor, Irene; Paterson, Andrew D.; Yuen, Ryan K. C.; Dastan, Jila; Stavropoulos, Dimitri J.; Howe, Jennifer L.; Thompson, Ann; Parlier, Morgan; et al.
Abstract: Autism spectrum disorder (ASD) is a relatively common childhood onset neurodevelopmental disorder with a complex genetic etiology. While progress has been made in identifying the de novo mutational landscape of ASD, the genetic factors that underpin the ASD's tendency to run in families are not well understood. In this study, nine extended pedigrees each with three or more individuals with ASD, and others with a lesser autism phenotype, were phenotyped and genotyped in an attempt to identify heritable copy number variants (CNVs). Although these families have previously generated linkage signals, no rare CNV segregated with these signals in any family. A small number of clinically relevant CNVs were identified. Only one CNV was identified that segregated with ASD phenotype; namely, a duplication overlapping DLGAP2 in three male offspring each with an ASD diagnosis. This gene encodes a synaptic scaffolding protein, part of a group of proteins known to be pathologically implicated in ASD. On the whole, however, the heritable nature of ASD in the families studied remains poorly understood.